Crypto-Asset. How Does Shariah Matter? - Mohd Ma’Sum Billah (Journal of Islamic Finance, 2022)
In the post-COVID era, it has further been observed that, fintech is extra-ordinarily among the fastest growing chapters in the eco-financial sectors and crypto-currency is not an exception. There are mixed views within the ambit of Shariah on the existing floating models of crypto-currencies bearing a common confusion on one’s intrinsic value and thus, whether they are compliant with Shariah? If not, what, and how the Shariah alternative solution may be in meeting the global Halal sentiment? The idea of crypto-asset is a new dimension with hypothetical discovery, which is quite different in nature as to crypto-currency (CC). The existing model of crypto-currency does not require an underlying asset to back the operation, while a crypto-asset in contrast, requires an underlying valued asset to back the operation and thus, positioning one bearing own intrinsic value. This paper, however, seeks to analyse the model structure, operational mechanisms, and possible Shariah review of crypto-asset (CA) within the principle of Maqasid al-Shariah. The research is expected to adapt hypothetical and META approaches by concluding with possible Shariah compliant strategic solution to crypto-asset in harmonizing with the contemporary eco-appreciation. The result of this research may be an added value to the current post-COVID eco-paradigm in creating an eco-opportunity for every level of people within the spirit of Maqasid al-Shariah.